Strategi Kepala Sekolah dalam Meningkatkan Mutu Pembelajaran Pendidikan Agama Islam - Mahmudah; Jumrodah; Atin Supriatin (Interdisciplinary Explorations in Research Journal, 2024)
The principal plays a crucial role in improving the quality of Islamic Religious Education (PAI) learning, aiming to shape students' character in accordance with Islamic values. This article examines principals' strategies in enhancing the quality of PAI learning through a literature review method of 10 selected journals from 2020-2023. Data were obtained using the Harzing’s Publish or Perish application with the keyword "Principals’ strategies to improve the quality of Islamic Religious Education learning." The review findings indicate that academic supervision, curriculum innovation, management of human resources and facilities, implementation of visionary and spiritual leadership, and the use of school-based management are the main strategies employed by principals. Academic supervision has proven effective in enhancing PAI teachers' competencies through observation and constructive feedback. Curriculum innovation relevant to contemporary needs also plays a significant role in creating high-quality learning. Furthermore, effective management of human resources and educational facilities fosters a conducive learning environment. These strategies are strengthened by visionary and spiritual leadership, oriented toward reinforcing Islamic values. These findings underline the importance of the principal's role in fostering PAI learning success through well-planned and innovative approaches.